Induction of HIV transcription by Nef involves Lck activation and protein kinase C[theta] raft recruitment leading to activation of ERK1/2 but not NF[kappa]B - Witte, Vanessa Alexandra; Laffert, Bernd; Gintschel, Patricia; Krautkrämer, Ellen; Blume, Katja; Fackler, Oliver Till; Baur, Andreas S. (The journal of immunology, 2008)
The Nef protein of HIV-1 is a key promoter of disease progression, owing to its dramatic yet ill-defined impact on viral replication. Previously, we have shown that Nef enhances embryonic ectodermal development Tat-mediated transcription in a manner depending on Lck and the cytoplasmic sequestration of the transcriptional repressor embryonic ectodermal development. In this study, we report that Lck is activated by Nef and targets protein kinase Cθ downstream, leading to the translocation of the kinase into membrane microdomains. Although microdomain-localized protein kinase Cθ is thought to induce the transcription factor NFκB, we unexpectedly failed to correlate Nef-induced signaling events with enhanced NFκB activity. Instead, we observed an increase in ERK MAPK activity. We conclude that Nef-mediated signaling cooperates with Nef-induced derepression and supports HIV transcription through an ERK MAPK-dependent, but NFκB-independent, pathway.
Im Titel sind "theta" und "kappa" als griechische Buchstaben dargestellt
Gesehen am 21.11.2019